SISTEM PENDIDIKAN MENURUT KONSEP ISLAM - Wendi Rais (JEM Jurnal Ekonomi dan Manajemen, 2019)
Education is a series of activities from a system. In the Islamic concept, education is known as tarbiyah, ta'lim, and ta'dib. As an Islamic education system has interrelated components. These components are the basis, objectives, educators, students, and Islamic education curriculum, its function is to ensure the achievement of the objectives of Islamic education. The supporting educational environment in the process of Islamic religious education needs to be considered because the environment is a place for students to carry out the education process (learning) and gain experience. The educational environment that has an atmosphere in accordance with the pattern of Islamic religious education is very helpful in carrying out the internalization of Islamic values ​​to students. Education can be said to be humanist and anticipatory if in the educational process between educators and students a communicative (dialogic atmosphere) situation makes students as subjects/agents of education rather than as objects of education. The essence of Islamic Education explained in the axiology of Islamic Education also has a future value that is intended to anticipate a better future, because educating means preparing a generation who will live and face future challenges that are far different from the previous period.